RELIGION AND FOLK BELIEFS - Mustafa SEVER (Zeitschrift für die Welt der Türken, 2011)
Folk beliefs, transmitted from generation to generation since the transfer from pre-writing and not included in any divine religion, but his side continued vitality of beliefs. Folk beliefs that have traditional as well as the local folk beliefs, include beliefs and practices, and personal features, divide two main types as a magic and experiential people’s beliefs. In this study we’ll focus on the qualities, differences and functions in everyday life of divine religion and folk beliefs and functions.